Soft Alloys Constructed with Distinct Mesoatoms via Self‐Sorting Assembly of Giant Shape Amphiphiles. Issue 19 (2nd March 2022) - Wang, Yicong; Huang, Jiahao; Yan, Xiao‐Yun; Lei, Huanyu; Liu, Xian‐You; Guo, Qing‐Yun; Liu, Yuchu; Liu, Tong; Huang, Mingjun; Bian, Fenggang; Su, Zebin; Cheng, Stephen Z. D.
Abstract: The packing structures of spherical motifs affect the properties of resultant condensed materials such as in metal alloys. Inspired by the classic metallurgy, developing complex alloy‐like packing phases in soft matter (also called "soft alloys") is promising for the next‐generation superlattice engineering. Nevertheless, the formation of many alloy‐like phases in single‐component soft matter is usually thermodynamically unfavourable and technically challenging. Here, we utilize a novel self‐sorting assembly approach to tackle this challenge in binary blends of soft matter. Two types of giant shape amphiphiles self‐sort to form their discrete spherical motifs, which further simultaneously pack into alloy‐like phases. Three unconventional spherical packing phases have been observed in these binary systems, including MgZn2, NaZn13, and CaCu5 phases. It's the first time that the CaCu5 phase is experimentally observed in soft matter. This work demonstrates a general approach to constructing unconventional spherical packing phases and other complex superlattices in soft matter. Abstract : Unconventional metal alloy‐originated superlattices with large volume asymmetry were successfully constructed in soft matter by blending binary giant shape amphiphiles, especially including a first experimentally observed CaCu5 phase in soft matter. Furthermore, the thermodynamic origin of these superlattices was also quantitatively analyzed by isoperimetric quotient.